Special section: Advancing customer experience and big data impact via academic- practitioner collaboration - Jamie Burton; Linda Nasr; Thorsten Gruber; Helen L. Bruce (2017)
Purpose This paper outlines the purpose, planning, development and delivery of the “1st AcademicPractitioner Research with Impact workshop: Customer Experience Management (CEM) and Big Data”, held at Alliance Manchester Business School on 18th and 19th January 2016, at which four subsequent papers were initially developed. Design/methodology/approach The paper sets out a summary of the importance and significance of the four papers developed at the workshop, and how the co-creative dialogue between managerial practitioners presenting key problems and issues that they face and carefully selected teams of academics was facilitated. Findings In order to develop richer and more impactful understanding of current problems challenging customer focused managers, there is a need for more dialogue and engagement between academics and practitioners. Practical implications The paper serves as a guideline for developing future workshops that aim at strengthening the links between academia and the business world. Originality/value This paper highlights the value of academic-practitioner workshops for focusing academic research on areas of importance for practitioners in order to generate impact. The innovative format of the workshop and the resulting impactful papers should serve as a call and motivation for future academic-practitioner workshop development.